Role of Teachers In Motivating Students to Learn Motivation In Class IV of SDN 003 Tambun Pelalawan - Selfi Kernelia; Febrina Dafit (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study examines the role of teachers in motivating learning among Class IV students at SDN 003 Tambun, Pelalawan. Learning motivation is a key factor influencing students’ engagement and academic participation, particularly at the elementary school level. Preliminary observations indicated that students’ motivation varied, with several learners showing low motivation, as reflected in passive behavior, limited participation, and low interest during classroom activities. Therefore, this study explores how teachers enact their roles as motivators in addressing these challenges. The present study employed a descriptive qualitative design conducted during the 2024/2025 academic year. The participants consisted of one fourth-grade classroom teacher as the primary informant and 18 Class IV students as supporting informants. Data were collected through classroom observations, semi-structured interviews, and documentation of instructional activities. Data were analyzed using an interactive analysis model that involved data reduction, data display, and drawing conclusions, while trustworthiness was ensured through source and technique triangulation. The findings revealed three main motivational strategies implemented by the teacher: providing encouragement and clear learning objectives, applying praise and positive reinforcement, and using varied teaching methods supported by learning media and individualized approaches. These strategies contributed to a more supportive and engaging learning environment. However, students’ learning motivation remained uneven, with some demonstrating low self-confidence and fear of making mistakes, which limited their active participation. In conclusion, teachers play a crucial role in motivating students’ engagement in learning. The findings provide practical implications for teachers in designing structured, emotionally supportive, and interactive learning environments to strengthen students’ confidence and sustain learning motivation in elementary classrooms.